An overview on WO3 based photocatalyst for environmental remediation. Issue 1 (February 2021) - Dutta, Vishal; Sharma, Sheetal; Raizada, Pankaj; Thakur, Vijay Kumar; Khan, Aftab Aslam Parvaz; Saini, Vipin; Asiri, Abdullah M.; Singh, Pardeep
Abstract: Environmental pollution and global energy demand require advanced photocatalytic materials such as visible-light-driven semiconductor photocatalysts. In particular, Tungsten oxide (WO3 ) appears promising candidate because of high absorption of visible light (up to 480 nm), its tunable bandgap, and outstanding optical properties. Fascinatingly, WO3 also hold advantages like nontoxic nature, economic cost, and stability in oxidative and acidic conditions. It is well-known that various synthetic procedures can be utilized for fabrication of a photocatalyst with different morphologies, sizes and structures which are dynamic on its catalytic performance to distinctive degrees. This review comprises several synthesis ways which are low-cost and environmentally friendly and detail analysis of the relationship between morphology control and photocatalytic performance of WO3 . Additionally, some top strategies for enhancing the photocatalytic performance of semiconductor WO3, like as elemental doping, hybridization with co-catalyst, heterojunction formation etc. are also summarized. Moreover, photocatalytic enhancement aspects and photocatalytic mechanisms of WO3 /semiconductor photocatalyst were elaborated. Lastly, the conclusion and main future prospects of WO3 -based semiconductor photocatalysts were deliberated. Graphical Abstract: ga1 Highlights: An outline on WO3 based photocatalytic systems is presented. Photocatalytic applications are discussed comprehensively. The environmental applications are elaborated. Future and prospects of WO3 photocatalyst are also discussed.